A 16-channel programmable SiPM bias supply system for Cherenkov telescope imaging camera. (1st January 2023) - Kumar, Sandeep; Upadhya, S.S.; Parmar, N.K.; Ranjan, M.; Nagesh, B.K.; Gothe, K.S.; Singh, B.B.; Rao, S.K.; Chitnis, V.; Acharya, B.S.; Bhatnagar, V.
Abstract: In recent years, the Silicon Photomultipliers (SiPMs) have emerged as a promising photodetector in various applications such as high energy physics, nuclear physics and medical instruments. One such application is in the pixelated camera of Imaging Atmospheric Cherenkov Telescopes (IACTs). IACTs are used to detect very high-energy celestial gamma rays using Atmospheric Cherenkov Technique. The SiPM gain is proportional to the overvoltage which is the difference between applied bias voltage and breakdown voltage. As the SiPM breakdown voltage increases with temperature, the overvoltage and hence the gain decreases proportionally (2-3%/°C) at a constant applied bias voltage. Also, the actual bias voltage across the SiPM changes with load current due to voltage drop across a series resistor in SiPM bias circuit, thus causing a change in overvoltage and gain. To maintain a constant gain of the SiPM, the applied bias voltage need to be adjusted to compensate for the changes in temperature and load. We are developing a 256-pixel imaging camera with SiPM as its photo-sensor. The camera will be placed at the focal point of telescope and will be operated during night in outdoor environment at Hanle, Ladakh, India. The night temperature at Hanle typically varies by ∼ 10°C overnight and ∼ 40°C (-20°C to +20°C) over the year. Thus, gain of SiPMs, exposed to the environment, may vary considerably during observations. A prototype 8-channel bias supply board with real time temperature & load compensation is developed to operate the camera SiPMs at fixed gain throughout the observation night. The voltage range of the bias supply for each channel is from 10 V to 80 V with 5 mV resolution and current upto 4 mA. The output voltage and current can be monitored with a resolution of ∼ 5 mV and ∼ 0.3 μA respectively. The single board computer, Raspberry Pi, is connected to the bias supply board over a 7-wire Customized Serial Peripheral Interface (CSPI) for control and monitoring. A multi-channel SiPM bias supply system is realized by daisy-chaining 8-channel boards through CSPI to cater bias voltage to all the pixels of the camera. The system is operated remotely using Ethernet interface of Raspberry-Pi. This paper discusses the design, development and performance of the prototype 16-channel closed-loop, programmable bias supply system with built-in compensation for changes in temperature and load.